CALCULATION RESEARCH ON THE RESIDUAL COMPRESSIVE STRENGTH OF STITCHED COMPOSITE LAMINATES AFTER IMPACT DAMAGE - CHEN Tao; XU XiWu; MAO ChunJian (Jixie qiangdu)
Stitched composite material not only suppresses delamination expansion, but also improves inter-laminar toughness and compressive characteristics after impact by introducing stitch in the thickness direction. Equivalent hole method simulates the initial damage of stitched plate. The finite element analysis method with damage evolution process based on threedimensional Hashin criterion with 3D solid element modelling laminates,3D bar element modelling stitch simulated the stitched composite laminates damage evolution effectively. The calculation results were in good agreement with the experimental data.